The Role of Return Migration in Revitalizing Rural Economies in Lebanon - Omar, Maha Hajj (Journal of Cultural Analysis and Social Change, 2026)
The concept of return migration is progressively becoming an integral enabler of the revitalization of rural economies. To understand the impact of this solution in the unique setting of Lebanon, this study attempts to assess the economic and social implications of returnees using a mixed-methods approach, with a quantitative survey targeting 100 Lebanese returnees and qualitative semi-structured interviews with eight Lebanese returnees’ entrepreneurs. The findings confirmed the imperative role of return migration on local revitalization, economic growth, job creation, and entrepreneurship support. Nevertheless, the findings highlighted key barriers that hinder maximized integration, including restricted access to capital, absence of formal institutional support programs, bureaucratic and infrastructural barriers. This study implies that rural revitalization is achievable through return migration, on the condition that there are collaborative efforts between returnees, their communities, and governmental bodies.